Improving the binding affinity of plastic degrading cutinase with polyethylene terephthalate (PET) and polyurethane (PU); an in-silico study - Deves Sabari V L; Gokulnath Rajmohan; Roshine S B; Srivaishnavi S; Kishore Nagasubramanian; Senthil Kumar G; Ponnusami Venkatachalam (Heliyon)
Plastic pollution is a worrying problem, and its degradation is a laborious process. Although enzymatic plastic breakdown is a sustainable method, drawbacks such as numerous plastic kinds of waste make the degradation challenging. Therefore, a multi-plastic degrading (MPD) enzyme becomes necessary. In this in-silico study, microorganisms and their enzymes that are known to degrade plastic polymers such as PET, PU, PVC, and PE were identified to assess their MPD capability. The cutinase of Thermobifida fusca was found to degrade both PET and PU polymers. The crystallized structure of cutinase was retrieved from PDB, and PET, PU ligands were docked using Schrodinger. However, the interactions between cutinase and the ligands were not efficient, as evidenced by the docking scores of −4.047 and −4.993 for PET and PU, respectively. Nevertheless, the interaction of the cutinase's active site with the ligands by hydrogen bond formation was promising. In this work, unconserved regions of cutinase were identified as potential mutation sites to enhance binding efficiency. In-silico Alanine Scanning Mutagenesis (ASM) and Site Saturation Mutagenesis (SSM) were performed as screening tests to find variants of cutinase with better docking scores for both ligands, specifically S136D, N28M, and S136Q. Molecular Dynamic Simulation (MDS) was performed for Wild Type (WT) cutinase, variants, and their respective complexes formed with the ligands. This simulation indicated the compactness, stability, and minimal energy of the variant complexes compared to WT complexes. Subsequent in vitro studies can ensure the improved degradation of both PET and PU by the variants.